Estimation of Heterogeneous Preferences, with an Application to Demand for Internet Services - Beckert, Walter (The Review of Economics and Statistics, 2005)
This paper presents a structural econometric framework for discrete and continuous consumer choices in which unobserved intrapersonal and interpersonal preference heterogeneity is modeled explicitly. It outlines a simulation-assisted estimation methodology applicable in this framework. This methodology is illustrated in an application to analyze data from the U.C. Berkeley Internet Demand Experiment.